Negative correlation of nodulation and grain production of beans (Phaseolus vulgaris) in soils where nitrogen is not limiting factor of plant growth - Pessanha, Gilberto G.; Franco, Avílio A.; Dobereiner, Johanna; Groszmann, Américo; Britto, Dirce P. P. de Souza (Pesquisa Agropecuaria Brasileira, 2014)
The significance, in three field experiments, of negative correlations between nodule weight and grain production of beans (Phaseolus vulgaris L.) was analyzed. Although nitrogen in these soils was not limiting to plant growth, there was some nitrogen fixation, as nodule weight in some of the cultivars was positively correlated with percent plant nitrogen content. The negative effect of nodulation on bean production was attributed to physiological disorders resulting from the Rhizobium - host association or to a commun mechanism of resistance to Rhizobium root infection and to certain pathogens related with empty pods the number of which was correlated with bean production. Due to the complexity and importance of the problem for bean production further studies are urgently needed.